"LA DIVISIÓN PERDIDA", UN FILM QUE NUNCA EXISTIÓ COMO TAL - Juan Bonifacio LORENZO BENAVENTE, (Fonseca, Journal of Communication, 2023)
The name of communist writer Clemente Cimorra (1900-1958), who was born in Oviedo, is related to the documentary Con la 43 división and a film wich also deals with la 43 División theme. The present article seeks to clarify certain confusion people have had about this up to now.